Empowering entrepreneurial communities and ecosystems case study insights - Fortunato, Michael W.-P. 1978- (Routledge, 2022)
"Entrepreneurial Communities and Ecosystems: Case Study Insights aims to provide applied examples that embody the theories, principles, and processes that contribute to empowering everyday entrepreneurial communities and ecosystems. Relying on a diversity of narratives from a wide range of entrepreneurial communities, entrepreneurial ecosystems, and organizations, this book presents a collection of case studies that take the reader inside the minds of leaders who are working to empower entrepreneurs and build entrepreneurial ecosystems and entrepreneurial communities-sometimes from scratch. The book features research and stories from entrepreneurs, development agencies, entrepreneurial support and assistance organizations (i.e. feeders and supports), governments, and involved citizens and local leaders in their quest to make their communities more entrepreneuring. The book presents an analytic frame through which the case studies are cross-analyzed, providing "meta-guidelines" for pursuing a broad range of strategies for supporting local and regional entrepreneurial action. This research volume is equally useful as an undergraduate or graduate text on the sociology of entrepreneurs and entrepreneurship as it is a field guide for ecosystem builders, policy makers, nonprofits, and entrepreneurship and social researchers worldwide"--
Keywords: Entrepreneurship; Entrepreneurship / Environmental aspects; Community development / Environmental aspects; Environmental policy; Entrepreneuriat; Entrepreneuriat / Aspect de l'environnement; Environnement / Politique gouvernementale; entrepreneurs; environmental policy